The integration between singing and acting skills and creative autonomy as the basic requirements for a scenic credibility in the classical singer's performance - Guse, Cristine Bello [UNESP] (Univ Federal Goias, 2018)
The article aims to point out that the singer's capability to integrate his/her singing and acting abilities and that the ability to perform his/her creative tasks in an autonomous manner are basic requirements for his/her performance to acquire scenic credibility in any aesthetic of presentation. In order to present arguments corroborating to this point, a brief review of the reflections on the scenic development of lyric singers performed by three important opera directors in the 20th century - Boris Goldovsky, Walter Felsenstein and Wesley Balk - is brought. The content of this article is part of the doctoral research in music made by the author.
Keywords: Scenic performance; Classical singer; Opera; Singing-acting